Shaping the earth erosion - Friend, Sandra (Friend, Sandra. Exploring planet earth., 2000)
Examines the different forces of erosion, such as wind, waves, acid rain, and glaciers, explains how they affect the topography of the earth, and describes their results, including dust storms, sand dunes, and caves.